Risk factors and surgical interventions associated with primary postpartum haemorrhage unresponsive to first-line therapies. (October 2014) - Yan, J.-Y.; Zhou, Z.-M.; Xu, X.; Huang, X.-Y.; Xu, R.-L.; Lin, S.-H.
Abstract The aim of this study was to investigate risk factors and surgical interventions associated with primary postpartum haemorrhage (PPH) unresponsive to first-line therapies. A retrospective analysis was performed of 212 women who experienced primary PPH (blood loss ≥ 500 ml). Logistic regression analysis identified that caesarean section (odds ratio [OR] 2.745; 95% confidence interval [CI], 1.063–7.085; p = 0.037) and abnormal placental adhesion (OR 3.823; 95% CI, 1.333–10.963; p = 0.013) were risk factors for PPH unresponsive to first-line therapies. There was no significant difference in blood loss, blood transfusion and success rate among intrauterine tamponade, B-Lynch suture and uterine artery ligation. Intrauterine tamponade is the least invasive and most rapid approach, so it should be taken as the first choice for surgical management after unresponsiveness to first-line therapies.